Microsoft Visual Basic 2010 developer's handbook - L(uml)offelmann, Klaus; Purohit, Sarika Calla; Safari eBooks (Sebastopol, CA : O'Reilly Media, 2011)
"This book is a reference on language concepts and features, as well as scenario-based guidance for putting Visual Basic to work. For use whether you're creating new applications with Visual Basic 2010 or upgrading projects built with an earlier version of the language"--P. [4] of cover.
Beginning with language and tools -- Beginners all-purpose symbolic instruction code -- Introduction to the .NET framework -- Sightseeing -- Introduction to Windows forms: designers and code editor by example -- Introduction to Windows Presentation Foundation -- The essential .NET data types -- Object-oriented programming -- A brief introduction to object-oriented programming -- Class begins -- First class programming -- Class inheritance and polymorphism -- Developing value types -- Typecasting and boxing value types -- Dispose, finalize, and the garbage collector -- Operators for custom types -- Events, delegates, and lambda expressions -- Enumerations -- Developing with generics -- Advanced types -- Programming with .NET framework data structures -- Arrays and collections -- Serialization -- Attributes and reflection -- Development simplifications in Visual Basic 2010 --Using my as a shortcut to common framework functions -- The application framework -- Language-integrated query: LINQ -- Introduction to LINQ (Language-Integrated Query) -- LINQ to objects -- LINQ to XML -- LINQ to entities : programming with entity framework -- Parallelizing applications -- Programming with the Task Parallel Library (TPL).
Description based on print version record.
Includes index.
Keywords: Microsoft Visual BASIC; BASIC (Computer program language); Electronic books